Structures of the human GTPase MMAA and vitamin B12-dependent methylmalonyl-CoA mutase and insight into their complex formation. - Froese, D; Kochan, G; Muniz, JR; Wu, X; Gileadi, C; Ugochukwu, E; Krysztofinska, E; Gravel, R; Oppermann, U; Yue, W (2010)
Vitamin B(12) (cobalamin, Cbl) is essential to the function of two human enzymes, methionine synthase (MS) and methylmalonyl-CoA mutase (MUT). The conversion of dietary Cbl to its cofactor forms, methyl-Cbl (MeCbl) for MS and adenosyl-Cbl (AdoCbl) for MUT, located in the cytosol and mitochondria, respectively, requires a complex pathway of intracellular processing and trafficking. One of the processing proteins, MMAA (methylmalonic aciduria type A), is implicated in the mitochondrial assembly of AdoCbl into MUT and is defective in children from the cblA complementation group of cobalamin disorders. To characterize the functional interplay between MMAA and MUT, we have crystallized human MMAA in the GDP-bound form and human MUT in the apo, holo, and substrate-bound ternary forms. Structures of both proteins reveal highly conserved domain architecture and catalytic machinery for ligand binding, yet they show substantially different dimeric assembly and interaction, compared with their bacterial counterparts. We show that MMAA exhibits GTPase activity that is modulated by MUT and that the two proteins interact in vitro and in vivo. Formation of a stable MMAA-MUT complex is nucleotide-selective for MMAA (GMPPNP over GDP) and apoenzyme-dependent for MUT. The physiological importance of this interaction is highlighted by a recently identified homoallelic patient mutation of MMAA, G188R, which, we show, retains basal GTPase activity but has abrogated interaction. Together, our data point to a gatekeeping role for MMAA by favoring complex formation with MUT apoenzyme for AdoCbl assembly and releasing the AdoCbl-loaded holoenzyme from the complex, in a GTP-dependent manner.